Predictive Value of Eosinophilia and Basophilia in the Diagnosis of Bronchopulmonary Dysplasia in Premature Infants - Buyukeren, Melek; Celik, Hasan Tolga; Yigit, Sule; Yurdakok, Murat (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVE: To compare the presence of eosinophilia and basophilia between two groups with and without bronchopulmonary dysplasia in preterm infants and, to investigate whether there was a correlation between the bronchopulmonary dysplasia severity and degree of eosinophilia. STUDY DESIGN: In this retrospective cohort study, we have evaluated premature babies who were admitted between 2007 and 2017 to the Neonatal Intensive Care Unit of Hacettepe Hospital. Hospital records were scanned and 85 preterm infants diagnosed with bronchopulmonary dysplasia formed the study group while 89 babies without bronchopulmonary dysplasia formed the control group. Necessary demographic, neonatal, and laboratory data were withdrawn from the electronic registry and patient files. RESULTS: In the study group, there was a statistically significant difference in the severity of eosinophilia and basophilia in the first day, first week, second week, third week, and fourth week compared to the control group (p<0.05). According to the mixed effect model, after adjusting results for gestational age and birth weight there was a statistically significant difference between groups in terms of eosinophil and basophil values (p<0.05). CONCLUSION: The number of eosinophils and basophils increased in patients with bronchopulmonary dysplasia without an increase in the number of leukocytes.